An Empirical Study to Determine Crop Insurance Premium Using Survival Analysis. Issue 1 (February 2021) - Hasanah, P; Azka, M; Herliansyah, R; Payung, N L
Abstract: Crop insurance provides a solution to economic losses experienced by farmers due to the risk of crop failure. The sample of crop survival data from Sukaratu Village in Cianjur-West Java had been analyzed. This research was analyzed the probability of failure based on the empirical study of the survival model. As a result, the probability of a crop failure studied in Sukaratu Village was calculated at 3.27%. Then, the exponential regression model was used to get the waiting time between crop failure events. The crop insurance product was simulated under the rate of premiums and benefits of insurance in several cases.